THE ROLE OF MEDICAL CLUSTERS IN REFORMING THE HEALTHCARE SYSTEM (International journal of artificial intelligence, 2025)
This article discusses consistent reforms in the healthcare system through the creation of modern medical clusters, the purpose of which is to provide specialized medical services to patients, increase the quantity and quality of innovative services and their convenience for the population. Important tasks are considered to be the effective use of state budget funds and state-owned objects.